Performance analysis of the PV module mitigation method affected by hotspot condition - Mohd Munif, Rosli; Mohd Shawal, Jadin; Mahfuzah, Mustafa; Norizam, Sulaiman; Mohd Shafie, Bakar (Institution of Engineering and Technology, 2022)
This paper presents the study analyses numerous mismatch mitigation techniques for the PV modules when affected by partial shading and hotspot condition. This evaluation serves as a guide for selecting appropriate techniques based on the associated needs and applications. Three types of mismatch mitigation techniques for PV modules were discussed. Benchmarking results show that power electronic-based (DC-DC Boost Converter) techniques are used to get the most power out of the system and to lessen the mismatch effect, but these techniques are a little more complicated to use and cost a lot and less effective in term of the waveform for current and voltage. A Fuzzy Logic Controller with DC-DC Boost Converter implementation was proposed as a solution to this problem. It was discovered that FLC with DC-DC Boost Converter retrieves more power than the other methods when the shading conditions are the same. Additionally, it is more dominant in terms of the waveform, where the performance of this method is 97.50%, which is an increase of 3.75% from the performance performed by the MPPT DC-DC Boost Converter. It also demonstrated that the MPPT based on FLC is robust, fast, and simple to implement.